A case report-management of concomitant acromion fracture with acromioclavicular joint dislocation - Thomas, Justin; J., Niranjan T. (International Journal of Research in Orthopaedics, 2025)
Shoulder injuries which comprises of simultaneous acromion fracture and acromioclavicular dislocations are rare injuries which were usually managed conservatively or sub optimally in previous times. These managements provided functional results with variable satisfaction. But in this era of grand armamentarium of fixation options we are trying a management option for these type of injuries. Here we present the case of 52 year old gentleman who met with a road traffic injury presented with right dominant side injury with pain and inability to move the shoulder. X-ray and CT evaluation done which yielded concomitant acromion fracture and acromioclavicular joint ligamentous dislocation. He was managed by fixation of acromion fracture by 4 holed 3.5 locking reconstruction plate and tightrope endo-button fixation of the acromioclavicular joint. As the said injury is a rare injury, literature references aided in decision making. Systematic approach to the injury along with a planned rehabilitation protocol yielded patient near normal pre injury level status of dominant side shoulder function. More literature must be published with variants of these fractures and varying fixation methods to attain a meta-analysis level for conclusive evidence.